Menke-Hennekam Syndrome: A Literature Review and a New Case Report - Aurora Sima; Roxana Elena Smădeanu; Anca Angela Simionescu; Florina Nedelea; Andreea-Maria Vlad; Cristina Becheanu (MDPI AG, 2022)
Background: Menke-Hennekam syndrome (MHS) is a rare and recently described syndrome consecutive to the variants in exon 30 or 31 in CREBBP (CREB-binding protein gene). The CREB-binding protein (CREBBP) and EP300 genes are two commonly expressed genes whose products possess acetyltransferase activity for histones and various other proteins. Mutations that affect these two genes are known to cause Rubinstein-Taybi syndrome (RTS); however, with the application of whole exome sequencing (WES) there were reports of variants that affect specific regions of exon 30 or 31 of these two genes but without the specific phenotype of RTS. Material and Methods: A review of the available literature was conducted, aimed at underscoring the difficulties in diagnosing MHS based on phenotype particularities. Results: Five applicable studies were identified by searching PubMed, Web of Science, and Scopus databases for publications up to November 2021 using the key terms "Menke-Hennekam syndrome" and "CREBBP". Conclusions: In this paper, we present a new case and highlight the importance of exome sequencing to identify different mutations of exons 30 and 31 of the CREBBP gene involved in MHS, and we make formal recommendations based on our literature review.